2022
DOI: 10.3390/jcdd9010023
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Utility of Apelin-to-NT-Pro-Brain Natriuretic Peptide Ratio for Heart Failure with Preserved Ejection Fraction among Type 2 Diabetes Mellitus Patients

Abstract: Background: Apelin is a regulatory vasoactive peptide, which plays a pivotal role in adverse cardiac remodeling and heart failure (HF) with reduced ejection fraction. The purpose of the study was to investigate whether serum levels of apelin is associated with HF with preserved election fraction (HFpEF) in patients with T2DM. Methods: The study retrospectively involved 101 T2DM patients aged 41 to 62 years (48 patients with HFpEF and 28 non-HFpEF patients). The healthy control group consisted of 25 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…ELISA was used to measure serum N terminal pro-B-type natriuretic peptide (NT-proBNP) and AP levels in all patients. The AP to NT-proBNP ratio was a better predictor of HFpEF in T2DM patients than AP or NT-proBNP alone [ 98 ]. Additionally, the prognostic value of AP levels has been investigated in CHF children.…”
Section: Apelinmentioning
confidence: 99%
“…ELISA was used to measure serum N terminal pro-B-type natriuretic peptide (NT-proBNP) and AP levels in all patients. The AP to NT-proBNP ratio was a better predictor of HFpEF in T2DM patients than AP or NT-proBNP alone [ 98 ]. Additionally, the prognostic value of AP levels has been investigated in CHF children.…”
Section: Apelinmentioning
confidence: 99%
“…Berezin AA, Fushtey IM, Berezin AE khi nghiên cứu NT Pro BNP huyết tương ở bệnh nhân đái tháo đường típ 2 có biến chứng suy tim phân suất tống máu bảo tồn nhận thấy dãn nhĩ (T) là một trong các yếu tố liên quan với HFpEF (OR là 1,2; p<0,05) [6]. Có lẽ độ cứng của cơ tim (titin), chất nền ngoại bào (xơ hóa), trương lực cơ tim, hình thái buồng tim ảnh hưởng rõ rệt chức năng tâm trương thất (T) trong suy tim phân suất tống máu bảo tồn do tăng áp lực đổ đầy tâm trương.…”
Section: Các Yếu Tố Liên Quan Với Suy Tim Phân Suất Tống Máu Bảo Tồn ...unclassified
“…Previous studies reported that both T2DM patients and HF patients had lower concentrations of irisin than do healthy individuals, whereas data on the alteration of circulating levels of apelin, myostatin and adropin in chronic HF patients depending on the presence of T2DM remain controversial [ 10 , 11 , 12 , 13 ]. However, there is evidence of the fact that irisin and apelin have yielded prognostic values for HFpEF regardless of NPs [ 14 , 15 ]. It is still uncertain whether altered glycemic control in T2DM patients with chronic HF corresponds to a difference in circulating levels of these myokines and whether the myokine profile should be considered as a marker of advanced disease.…”
Section: Introductionmentioning
confidence: 99%